A pragmatic approach for mortality prediction after surgery in infective endocarditis: optimizing and refining EuroSCORE. (October 2018) - Fernández-Hidalgo, N.; Ferreria-González, I.; Marsal, J.R.; Ribera, A.; Aznar, M.L.; de Alarcón, A.; García-Cabrera, E.; Gálvez-Acebal, J.; Sánchez-Espín, G.; Reguera-Iglesias, J.M.; De La Torre-Lima, J.; Lomas, J.M.; et al.
Abstract: Objective: To simplify and optimize the ability of EuroSCORE I and II to predict early mortality after surgery for infective endocarditis (IE). Methods: Multicentre retrospective study ( n = 775). Simplified scores, eliminating irrelevant variables, and new specific scores, adding specific IE variables, were created. The performance of the original, recalibrated and specific EuroSCOREs was assessed by Brier score, C-statistic and calibration plot in bootstrap samples. The Net Reclassification Index was quantified. Results: Recalibrated scores including age, previous cardiac surgery, critical preoperative state, New York Heart Association >I, and emergent surgery (EuroSCORE I and II); renal failure and pulmonary hypertension (EuroSCORE I); and urgent surgery (EuroSCORE II) performed better than the original EuroSCOREs (Brier original and recalibrated: EuroSCORE I: 0.1770 and 0.1667; EuroSCORE II: 0.2307 and 0.1680). Performance improved with the addition of fistula, staphylococci and mitral location (EuroSCORE I and II) (Brier specific: EuroSCORE I 0.1587, EuroSCORE II 0.1592). Discrimination improved in specific models (C-statistic original, recalibrated and specific: EuroSCORE I: 0.7340, 0.7471 and 0.7728; EuroSCORE II: 0.7442, 0.7423 and 0.7700). Calibration improved in both EuroSCORE I models (intercept 0.295, slope 0.829 (original); intercept –0.094, slope 0.888 (recalibrated); intercept –0.059, slope 0.925 (specific)) but only in specific EuroSCORE II model (intercept 2.554, slope 1.114 (original); intercept –0.260, slope 0.703 (recalibrated); intercept –0.053, slope 0.930 (specific)). Net Reclassification Index was 5.1% and 20.3% for the specific EuroSCORE I and II. Conclusions: The use of simplified EuroSCORE I and EuroSCORE II models in IE with the addition of specific variables may lead to simpler and more accurate models.